2017
DOI: 10.4022/jafib.1553
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of intracardiac echocardiography for atrial flutter ablation is associated with reduced fluoroscopy time, but not with a reduction of radiofrequency energy delivery time

Abstract: The use of ICE for atrial flutter ablation is associated with less fluoroscopy time and improved ability to achieve bidirectional block compared to traditional conventional flutter ablation methods. However, it is not asoociated with reduced ablation time or overall procedure duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…The significant reduction in fluoroscopy time demonstrated in the main analysis was robust in all sensitivity testing, including studies with only AF patients (Hedges' g −1.25; 95% CI −2.14 to −0.36; P < .01) 10,11,24,26–31,37,38 . (Table S3).…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…The significant reduction in fluoroscopy time demonstrated in the main analysis was robust in all sensitivity testing, including studies with only AF patients (Hedges' g −1.25; 95% CI −2.14 to −0.36; P < .01) 10,11,24,26–31,37,38 . (Table S3).…”
Section: Resultsmentioning
confidence: 78%
“…Ten studies reported fluoroscopy dose data, with significant heterogeneity among studies (I 2 = 93%) and no evidence of publication bias or small study effects 23–28,31,33,37,38 . Use of ICE in ablation procedures showed significant reductions in fluoroscopy dose vs ablation without the use of ICE (Hedges' g −1.27; 95% CI −1.91 to −0.62; P < .01) (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations